Breakthrough Invasive Fungal Infections in Allogeneic Hematopoietic Stem Cell Transplantation - Carmine Liberatore; Francesca Farina; Raffaella Greco; Fabio Giglio; Daniela Clerici; Chiara Oltolini; Maria Teresa Lupo Stanghellini; Federica Barzaghi; Paolo Vezzulli; Elena Orsenigo; Consuelo Corti; Fabio Ciceri; et al. (Journal of Fungi, 2021)
Despite the recent introduction of mold-active antifungal prophylaxis (MAP), breakthrough invasive fungal infections (b-IFI) still represent a possible complication and a cause of morbidity and mortality in hematological patients and allogeneic hematopoietic stem-cell transplantation recipients (HSCT). Data on incidence and type of b-IFI are limited, although they are mainly caused by non-fumigatus Aspergillus and non-Aspergillus molds and seem to depend on specific antifungal prophylaxis and patients’ characteristics. Herein, we described the clinical presentation and management of two cases of rare b-IFI which recently occurred at our institution in patients undergoing HSCT and receiving MAP. The management of b-IFI is challenging due to the lack of data from prospective trials and high mortality rates. A thorough analysis of risk factors, ongoing antifungal prophylaxis, predisposing conditions and local epidemiology should drive the choice of antifungal treatments. Early broad-spectrum preemptive therapy with a lipid formulation of amphotericin-B, in combination with a different mold-active azole plus/minus terbinafine, is advisable. The therapy would cover against rare azole-susceptible and -resistant fungal strains, as well as atypical sites of infections. An aggressive diagnostic work-up is recommended for species identification and subsequent targeted therapy.